An Exploratory Study of the Factors Associated With Literacy Teachers' Integration of Technology: A Study of Lebanese Schools. Issue 4 (1st October 2016) - Chaaban, Youmen; Moloney, Robyn
Abstract: The purpose of this study is to explore Lebanese teachers' perceptions of the factors determining their integration of technology into literacy classrooms. A quantitative survey examining literacy teachers' individual characteristics and their perceptions of contextual factors was conducted at Lebanese schools. The survey collected data on the levels of reported technology integration, technology availability and support, provision of formal training, and teachers' perceptions of their pedagogical, self-efficacy, and value beliefs. Qualitative data collected using interviews provided in-depth data and added a personal perspective to the quantitative results. The analysis of the data included descriptive statistics and thematic analysis, which together led to identifying several factors determining technology integration in the Lebanese literacy classroom. Results indicated relatively low levels of integration and consistent perceptions about the barriers hindering such integration. Recommendations are suggested to advance school leaders' and teacher trainers' understanding of the factors that need to be considered to better support teachers in creating technology-enhanced classrooms.